Unstable Infected Fractures and Spinal Stability: A Critical Role in Treatment - Khurram Shehzad, Zia Ullah, Tauseef Raza, Aurangzeb Kalhoro, Akkad Rafiq, Junaid Javaid, Mian Iftikhar Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An uncommon infection of the spinal column that can be caused by either bacteria or fungi is known as vertebral osteomyelitis. Objective: Aim of current study was to determine the importance of spinal stability among patients of unstable infected fractures. Methods: Total patients of unstable infected were presented in this study. Patients were included after getting informed written consent. All the patients were underwent for minimal invasive surgery. Post-surgery outcomes among all cases were assessed. SPSS 22.0 was used to analyze all data. Results: There were majority 37 (61.7%) males and 23 (38.3%) females among all cases. The mean age of the presented cases was 58.9 years and had mean BMI 26.5 kg/m2. 32 cases had DM, 20 cases had hypertension and 8 cases had smoking history. Road traffic accident was the most common cause of fracture found in 35 (58.3%). Post-treatment, 27 (45%) cases showed excellent results, 15 (25%) showed good and 13 (21.7%) cases showed fair outcomes. Poor outcomes were only resulted in 5 patients. Conclusion: We concluded in this study that spinal stability is necessary to treat the unstable infected fractures. The healing process is impeded by instability, which leads to a vicious circle of damaged soft-tissue, impaired neovascularity, and osteolysis. Keywords: vertebral osteomyelitis, spinal stability, outcomes